El papel del componente superestructural en la elaboración de las macroestructuras - González Moreyra, Raúl (2001)
Sixty two university students were examined in terms of their comprehension of three types of texts: narrative, argumentative and expositive. An instrument which applied a neologism technique was used to measure the differential performance in the three types of textual superstructure. It was found that the expositive text was the one that posed greater difficulties, followed the argumentative and the narrative. A developmental explanation is given for these results. Furthermore, it was found that sample variables such as gender, age, area of studies, achievement both in school and in the university entry exam, and educational level of parents, did not produce significant differences in the results. Finally, the neologism technique applied had a good level of confidence and validity.